The Clinical and Metabolic Profiles in Menstrual Changes Among Reproductive‐Aged Women Post‐COVID‐19 - Wei Wang; Manfei Si; Xinyu Qi; Hongxia Hu; Xiaole Sun; Juyan Liang; Jianghua Zhou; Xianmin Bi; Wei Zhao; Yuanyuan Wang; Liying Yan; Rong Li; et al. (MedComm)
ABSTRACT Menstruation is a key indicator of female reproductive health, yet clinical features and underlying mechanisms associated with menstrual changes following the coronavirus disease 2019 (COVID‐19) infection remain unclear. Here, we recruited 253 participants through questionnaires, and 73 individuals underwent metabolomic analysis of blood serum. Over 60% reported menstrual changes, primarily experiencing longer cycle and lighter bleeding, which were significantly associated with age, general medical conditions, perceived stress, anxiety scores, and depression scores, as well as COVID‐19 symptoms including fatigue and headache. General medical conditions were the sole independent risk factor for any menstrual changes. Metabolomic analysis highlighted disturbances in steroid hormone biosynthesis. We identified 52 significantly differential metabolites between groups with and without any menstrual changes (AnyC vs. NoC), with high discrimination achieved by combining phenylglyoxylic acid, PC O‐40, traumatic acid, and estrone sulfate. Furthermore, several significantly upregulated metabolites were closely correlated with estradiol (E2) levels, including estrone sulfate, which was also positively correlated with T levels. Specifically, T levels decreased with recovery duration in the AnyC group (p = 0.0015). Collectively, our findings uncovered key clinical factors and metabolic disruptions in menstrual changes, underscoring potential adverse long‐term effects of COVID‐19 on women's health.